Highly Efficient, Cost Effective, and Safe Sodiation Agent for High‐Performance Sodium‐Ion Batteries - Shanmukaraj, Devaraj; Kretschmer, Katja; Sahu, Tuhin; Bao, Weizhai; Rojo, Teofilo; Wang, Guoxiu; Armand, Michel (ChemSusChem, 2018)
The development of sodium‐ion batteries has been hindered so far by the large irreversible capacity of hard carbon anodes and other anode materials in the initial few cycles, as sodium ions coming from cathode materials is consumed in the formation of the solid–electrolyte interface (SEI) and irreversibly trapped in anodes. Herein, the successful synthesis of an environmentally benign and cost‐effective sodium salt (Na2C4O4) is reported that could be applied as additive in cathodes to solve the irreversible‐capacity issues of anodes in sodium‐ion batteries. When added to Na3(VO)2(PO4)2F cathode, the cathode delivered a highly stable capacity of 135 mAh g−1 and stable cycling performance. The water‐stable Na3(VO)2(PO4)2F cathode in combination with a water‐soluble sacrificial salt eliminates the need for using any toxic solvents for laminate preparation, thus paving way for greener electrode fabrication techniques. A 100 % increase in capacity of sodium cells (full‐cell configuration) has been observed when using the new sodium salt at a C‐rate of 2C. Regardless of the electrode fabrication technique, this new salt finds use in both aqueous and non‐aqueous cathode‐fabrication techniques for sodium‐ion batteries. A new added flavor: A new sodiation agent (Na2C4O4) demonstrates a capability to significantly improve the performance of cathode materials in sodium‐ion batteries. The as‐synthesized sodium salt can effectively replace other commercial salts (such as NaN3, Na3P, and Na2CO3) and exhibits superior efficiency compared to these salts in improving capacity and rate capability of sodium cathodes as well as compensating the first charge irreversibility of anodes.